MARKET MANAGEMENT OF LIVESTOCK PRODUCTS ON THE EXAMPLE OF RK (ON THE EXAMPLE OF EKO) - B.S. Korabayev,; A.A. Nurgaliyev,; A.A. Amanbayeva,; K.K. Baygabulova,; E.K. Moldakenova, (Academic Journal of Physical and Chemical Sciences, 2019)
Livestock makes an important contribution to the food supply in rural and urban areas and promotes family nutrition by providing animals with protein. As household income grows, protein intake, mainly of animal origin, increases, which makes it possible to replace vegetable protein with animals. In addition to milk, eggs and meat used as a source of food, other livestock products, such as hides, skins and horns, are used for home consumption and local sale. Livestock is closely related to crop production. The use of livestock and manure offal is important in crop production. Livestock is a source of energy that provides animal cravings, while manure improves soil structure and fertility, and retains moisture. Both uses are environmentally friendly, improving the circulation of energy and nutrients.